Multimodal neurophenomenology of advanced concentration absorption meditation: An intensively sampled case study of Jhana - Chowdhury, Avijit; Bianciardi, Marta; Chapdelaine, Eric; Riaz, Omar S.; Timmermann, Christopher; van Lutterveld, Remko; Sparby, Terje; Sacchet, Matthew D. (NeuroImage (Orlando, Fla.), 2025)
•This multimodal [ultra-high-field 7T MRI, electroencephalography (fMRI-EEG)] intensively sampled neurophenomenological study in a rare adept meditator offers the most comprehensive view of the brain dynamics of advanced concentration meditation.•Global hyperconnectivity, collapsed modular integrity of the brain's functional networks (fMRI), widespread decreases in broadband EEG oscillatory power, and increases in Lempel-Ziv complexity (LZ, a measure of entropy) were observed during these meditative states – metrics that also correlated with the blissful experience.•These results enrich our understanding of these advanced meditative states and support the notion that advanced meditation may deconstruct the hierarchical organization of the brain's function. Using a combination of fMRI, EEG, and phenomenology ratings, we examined the neurophenomenology of advanced concentrative absorption meditation, namely jhanas (ACAM-J), in a practitioner with over 23,000 h of meditation practice. Our study shows that ACAM-J states induce reliable changes in conscious experience and that these experiences are related to neural activity. Using resting-state fMRI functional connectivity, we found that ACAM-J is associated with decreased within-network modularity, increased global functional connectivity (GFC), and desegregation of the default mode and visual networks. Compared to control tasks, the ACAM-J were also related to widespread decreases in broadband EEG oscillatory power and increases in Lempel-Ziv complexity (LZ, a measure of brain entropy). Some fMRI findings varied by the control task used, while EEG results remained consistent, emphasizing both shared and unique neural features of ACAM-J. These differences in fMRI and EEG-measured neurophysiological properties correlated with specific changes in phenomenology – and especially with ACAM-J-induced states of bliss - enriching our understanding of these advanced meditative states. Our results show that advanced meditation practices markedly dysregulate high-level brain systems via practices of enhanced attention to sensations, corroborating recent neurocognitive theories of meditation as the deconstruction of the brain's cortical hierarchy. Overall, our results suggest that ACAM-J is associated with the modulation of large-scale brain networks in both fMRI and EEG, with potential implications for understanding the mechanisms of deep concentration practices and their effects on subjective experience. [Display omitted]